Country-Brand Fit: The Effect of COO Stereotypes and Brand Positioning Consistency on Consumer Behavior: Evidence From EEG Theta-Band Oscillation - Wang, Ailian; Lyu, Dong; Liu, Yunlu; Liu, Jiaoyang; Gao, Li; Jin, Jia (Frontiers in Neuroscience, 2022)
Grounded on the cognitive consistency theory, this paper adopts the prime-probe paradigm and Electroencephalography (EEG) experiment to examine the impact of country-of-origin (COO) stereotypes-brand positioning congruence on consumer behavior, the boundary effect of brand positioning strategy, as well as the underlying cognitive mechanism. Behaviorally, consumers show a higher purchase intention in the congruence condition. Moreover, this congruence effect of purchase intention can be found for competence brand positioning strategies rather than warmth brand positioning strategies. At the brain level, we found that compared with the congruence condition, the incongruence condition enhances consumers' cognitive conflict, reflected in enhanced frontal theta-band oscillation. Furthermore, the cognitive conflict effect is accentuated in the competence positioning strategy condition rather than the warmth strategy positioning condition, confirming the boundary effect of brand positioning strategy from the brain level. These findings provide neural evidence that the congruence between COO stereotypes and brand positioning influences consumer purchase behavior, reveals a boundary effect in the COO stereotype-brand positioning congruence, and highlights the importance of the competence dimension. Finally, the theoretical and practical implications are discussed.